The Osteocyte as the New Discovery of Therapeutic Options in Rare Bone Diseases - Pathak, Janak L.; Bravenboer, Nathalie; Klein-Nulend, Jenneke (Frontiers in Endocrinology, 2020)
Osteocytes are the most abundant (~95%) cells in bone with the longest half-life (~25 years). In the past osteocytes have been regarded as vestigial cells in bone, since they are buried inside the tough bone matrix. However, during the last 30 years it has become clear that osteocytes are as important as bone forming osteoblasts and bone resorbing osteoclasts in maintaining bone homeostasis. The osteocyte cell body and dendritic processes reside in bone in a complex lacuno-canalicular system, which allows the direct networking of osteocytes to their neighboring osteocytes, osteoblasts, osteoclasts, bone marrow, blood vessels, and nerves. Mechanosensing of osteocytes translates the applied mechanical force on bone to cellular signaling and regulation of bone adaptation. The osteocyte lacuno-canalicular system is highly efficient in transferring external mechanical force to the osteocyte cell body and dendritic processes via displacement of fluid in the lacuno-canalicular space. Osteocyte mechanotransduction regulates the formation and function of osteoblasts and osteoclasts to maintain bone homeostasis. Osteocytes produce a variety of proteins and signaling molecules such as sclerostin, cathepsin K, Wnts, DKK1, DMP1, IGF1, and RANKL/OPG to regulate osteoblast and osteoclast activity. Various genetic abnormality-associated rare bone diseases are related to disrupted osteocyte functions, including sclerosteosis, van Buchem disease, hypophosphatemic rickets, and WNT1 and plastin3 mutation-related disorders. Meticulous studies during the last 15 years on disrupted osteocyte function in rare bone diseases guided for the development of various novel therapeutic agents to treat bone diseases. Studies on genetic, molecular, and cellular mechanisms of sclerosteosis and van Buchem disease revealed a role for sclerostin in bone homeostasis, which led to the development of sclerostin antibody to treat osteoporosis and other bone degenerative diseases. The mechanism of many other rare bone diseases and the role of the osteocyte in the development of such conditions still needs to be investigated. In this review, we mainly discuss the knowledge obtained during the last 30 years on the role of the osteocyte in rare bone diseases. We speculate about future research directions to develop novel therapeutic drugs targeting osteocyte functions to treat both common and rare bone diseases.